2021
DOI: 10.1096/fj.202002029r
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial bioenergetic pathways in blood leukocyte transcriptome decrease after intensive weight loss but are rescued following weight regain in female physique athletes

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…In support of this contention, we observed a decline in resting heart rate in both sexes, which has previously been connected to changes in the autonomous nervous system during adaptive thermogenesis (Rosenbaum and Leibel, 2010). Moreover, we reported a temporary suppression of the immune (Sarin, Gudelj, et al, 2019) and reproductive (Hulmi et al, 2017) systems and decreased levels of systemic inflammation (Sarin, Lee, et al, 2019), and using leukocyte transcriptomics, repressed mitochondrial oxidative function and protein translation (Sarin et al, 2021) during contest preparation in our earlier female physique athlete study. It has also been questioned whether adaptive thermogenesis only exists during an energy deficit (Martins et al, 2020), but in the aforementioned studies, the participants had already been in energy balance due to the last week of competition preparation, and still many of the fat-loss -induced physiological and molecular mechanisms behind adaptive thermogenesis were still present (Hulmi et al, 2017;Sarin, Gudelj, et al, 2019;Sarin, Lee, et al, 2019;Sarin et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…In support of this contention, we observed a decline in resting heart rate in both sexes, which has previously been connected to changes in the autonomous nervous system during adaptive thermogenesis (Rosenbaum and Leibel, 2010). Moreover, we reported a temporary suppression of the immune (Sarin, Gudelj, et al, 2019) and reproductive (Hulmi et al, 2017) systems and decreased levels of systemic inflammation (Sarin, Lee, et al, 2019), and using leukocyte transcriptomics, repressed mitochondrial oxidative function and protein translation (Sarin et al, 2021) during contest preparation in our earlier female physique athlete study. It has also been questioned whether adaptive thermogenesis only exists during an energy deficit (Martins et al, 2020), but in the aforementioned studies, the participants had already been in energy balance due to the last week of competition preparation, and still many of the fat-loss -induced physiological and molecular mechanisms behind adaptive thermogenesis were still present (Hulmi et al, 2017;Sarin, Gudelj, et al, 2019;Sarin, Lee, et al, 2019;Sarin et al, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…Despite the association between VLCSFAs and positive health outcomes, studies using cultured myotubes and animal models have demonstrated that exposure to circulating SFAs, especially VLCSFAs, have promoted the formation of ceramides [ 49 , 50 ], while unsaturated FFAs have prevented excess ceramide accumulation stimulated by SFAs. Previously, ceramides have been shown to suppress the electron transport chain and oxidative functions in mitochondria, thus inducing the production of reactive oxygen species—a finding that was subsequently suggested by us through integrative analysis of NMR-metabolomics and leukocyte transcriptomics on the same study population of female physique athletes after weight loss [ 51 ]. Interestingly, metabolic states of chronic malnutrition and thus low-energy availability have also been characterized by dysfunction of peroxisomal β-oxidation and the accumulation of VLCFAs [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study is a sub-study of a larger Physique Athlete Study conducted by the University of Jyväskylä including a cohort collected in 2015–2016 [ 12 , 13 , 14 , 15 ] and 2019–2020 (Isola et al submitted for revision, ClinicalTrials.gov ID: NCT04392752). The current study looked at the prevalence of energy availability and the distribution of intake of different energy nutrients.…”
Section: Methodsmentioning
confidence: 99%
“…In contrary, low EA (<30 kcal/kg of FFM) is necessary for weight loss, but may negatively affect the performance, the production of various hormones and bone health [ 10 , 11 ] and thus may lead to a multisyndrome condition called relative energy deficiency in sport (RED-S) [ 10 ]. Studies investigating weight loss in these athletes have shown that low EA may suppress leptin, triiodothyronine (T3), testosterone, and estradiol concentrations, and increase the incidence of menstrual irregularities, including amenorrhea [ 12 ] markers of immunosuppression [ 13 ], and adaptive thermogenesis [ 14 ]. Furthermore, amenorrhea, which is considered to be a long-term marker for low EA [ 10 ], impairs bone health, increases the risk for bone stress injury and cardiovascular disease [ 11 ], and may thus, through these effects, alter athletes’ performance and health.…”
Section: Introductionmentioning
confidence: 99%